Remineralization of human natural caries and artificial caries-like lesions with an experimental whisker-reinforced ART-composite - Yang, Bin (2011)
To compare the remineralization of human natural caries and artificial caries-like dentin lesions from a novel whisker-reinforced experimental composite resin to a resin-modified glass ionomer cement (RM-GIC) as control. Ten molars with moderate natural dentin caries were prepared (N). Artificial caries-like dentin lesions were prepared in occlusal dentin of ten caries-free molars and demineralized at pH=4.3 for 48 h (A). The cavities were restored with ART-composite or RM-GIC. All restored teeth were sliced into 120-μm sections. Transverse microradiography combined with digital image analysis was performed to analyze the change in mineral density at the same position of the specimens before, after 4 weeks and 8 weeks remineralization/demineralization treatment. The mean percent remineralization ± standard deviation after 4 weeks and 8 weeks are: N: ART-composite: 27±9, 46±14; RM-GIC: 18±6, 36±11; A: ART-composite: 48±9, 66±11; RM-GIC: 50±13, 62±11. For the remineralization of natural caries, there was a significant difference between ART-composite and RM-GIC (p<0.05). For both restoratives there were significant differences between remineralization of natural and artificial caries (p<0.001). ART-composite and RM-GIC remineralized natural and artificial caries differently most likely due to differences in microstructure and composition of caries dentin.